Properties of Carry Value Transformation. (1st April 2012) - Pal, Suryakanta; Sahoo, Sudhakar; Nayak, Birendra Kumar
Abstract : Carry Value Transformation (CVT) is a model of discrete deterministic dynamical system. In the present study, it has been proved that (1) the sum of any two nonnegative integers is the same as the sum of their CVT and XOR values. (2) the number of iterations leading to either CVT = 0 or XOR = 0 does not exceed the maximum of the lengths of the two addenda expressed as binary strings. A similar process of addition of modified Carry Value Transformation (MCVT) and XOR requires a maximum of two iterations for MCVT to be zero. (3) an equivalence relation is shown to exist on Z × Z which divides the CV table into disjoint equivalence classes.